Implementation of Experiential Learning Methods in Environmental Education - Aribowo, Suryo; Nadiroh, Nadiroh; Faesal, Muhammad (IJBLE Scientific Publications Community Inc., 2025)
This study aims to explain the development of environmental education from an ecopedagogical perspective and its implementation using an experiential learning approach. This research employs a descriptive method and utilizes library research by collecting, studying, and analyzing various research findings in the form of journals, books, and government documents relevant to the research topic. The environmental movement of the 1960s-1970s advocated for environmental issues in response to resource exploitation, which exacerbated social and economic inequalities. This pressure led to the emergence of the concept of sustainable development and the integration of environmental education into curricula. However, such education tends to be elitist and lacks practical action, necessitating a return to its praxis roots through ecopedagogy and experiential learning. This approach emphasizes learning based on direct experience, such as sustainable agriculture practices or eco-friendly energy applications, which are relevant to community conditions. Collaboration among the government, private sector, and educational institutions is essential to ensure the effectiveness of this program, ultimately fostering a more inclusive and action-oriented environmental awareness.